Association of ventilation with outcomes from out-of-hospital cardiac arrest. (August 2019) - Chang, Mary P.; Lu, Yuanzheng; Leroux, Brian; Aramendi Ecenarro, Elisabete; Owens, Pamela; Wang, Henry E.; Idris, Ahamed H.
Abstract: Aim of study: To determine the association between bioimpedence-detected ventilation and out-of-hospital cardiac arrest (OHCA) outcomes. Methods: This is a retrospective, observational study of 560 OHCA patients from the Dallas-Fort Worth site enrolled in the Resuscitation Outcomes Consortium Trial of Continuous or Interrupted Chest Compressions During CPR from 4/2012 to 7/2015. We measured bioimpedance ventilation (lung inflation) waveforms in the pause between chest compression segments (Physio-Control LIFEPAK 12 and 15, Redmond, WA) recorded through defibrillation pads. We included cases ≥18 years with presumed cardiac cause of arrest assigned to interrupted 30:2 chest compressions with bag-valve-mask ventilation and ≥2 min of recorded cardiopulmonary resuscitation. We compared outcomes in two a priori pre-specified groups: patients with ventilation waveforms in <50% of pauses (Group 1) versus those with waveforms in ≥50% of pauses (Group 2). Results: Mean duration of 30:2 CPR was 13 ± 7 min with a total of 7762 pauses in chest compressions. Group 1 (N = 424) had a median 11 pauses and 3 ventilations per patient vs. Group 2 (N = 136) with a median 12 pauses and 8 ventilations per patient, which was associated with improved return of spontaneous circulation (ROSC) at any time (35% vs. 23%, p < 0.005), prehospital ROSC (19.8% vs. 8.7%, p < 0.0009), emergency department ROSC (33% vs. 21%, p < 0.005), and survival to hospital discharge (10.3% vs. 4.0%, p = 0.008). Conclusions: This novel study shows that ventilation with lung inflation occurs infrequently during 30:2 CPR. Ventilation in ≥50% of pauses was associated with significantly improved rates of ROSC and survival.